0443 Arousal Duration Is A Trait in Sleep Apnea. (12th April 2019) - Cunningham, Laura; Dunham, Kelley; Shuttari, Nida; Thomas, Robert Joseph
Abstract: Introduction: Several features of the polysomnogram in patients with obstructive sleep apnea have strong trait-like characteristics. Thee include upper airway collapsibility, arousal threshold, loop gain, the upper airway negative pressure response, REM vs. NREM dominance of apnea, sleep depth post-arousal, and sleep fragmentation propensity. Arousal counts dominate clinical practice but arousal duration may have information on sleep quality and trait sleep fragmentation propensity. Methods: Split night polysomnograms performed at the Beth Israel Deaconess Medical Center affiliated sleep laboratories were scored for arousal duration, besides standard scoring metrics. Arousal duration for this analysis was defined at the time to the first slow oscillation (not time to any feature of sleep). This included the first K-complex post arousal or a slow wave with at least the following characteristics: 0.5 Hz and 50 microvolts amplitude. Statistical analysis compared the diagnostic and treatment (CPAP) components. Intra-class coefficients were generated for several measures. Results: The population characteristics included age: 51 +/- 12.2, 113 male, and BMI 34.6 +/- 3.5. Total sleep time for diagnostic and titration components was 126 +/- 51.6 and 225.6 +/- 105.6 minutes; sleep efficiency 71.7 +/- 17.2 and 74 +/- 18, respectively. The arousal index was 41.7 +/- 24.9 vs. 22.3 +/- 16 / hour of sleep. The AHI was 58 +/- 28.4 and 20.4 +/- 16/hour of sleep. The mean arousal duration was 12.6 +/- 5.6 and 13.9 +/- 6 seconds. The ICC for NREM arousal duration was 0.71. The ICC for N3 was 0.02, for N1 0.04, and 0, 30 for arousal index, considering the baseline and titration components. Conclusion: Arousal duration as characterized by return to NREM slow-oscillation is a trait in OSA. The conventional arousal index and default scoring of 3-second arousals discard potentially useful information. Support (If Any): American Sleep Medicine Foundation